Detection of avian influenza A virus in Malaysian birds - Rahim, Z.A; Rahman, M.A; Ahmad, I. (Research Journal of Pharmaceutical, Biological and Chemical Sciences, 2015)
A study was conducted to assess the presence of avian influenza A virus (AIV A) especially in wild forest birds of Malaysia. The annual north-south movements of migratory birds have been implicated as a factor that contributes to the spread of AIV A throughout the world. Mixing of local forest birds and migratory birds has been reported to occur during migrational stops of the migratory birds. It has been postulated that infected wild birds can pass on the virus to poultry, especially at areas that are considered as interface between wild birds and the domesticated poultry reared at the forest fringes. The possible widespread of AIV A in Malaysia and reports of outbreaks of H5N1 strain during the early 2003 to 2006, have led to the interest in finding support for this postulate. Occurrence of AIV A was postulated with possible implications with the ecological parameters of the areas. Transmission of viruses had been speculated to occur in certain seasons which give rise to the idea that some climatic factors such as temperature and rainfall plays their role in the transmission. Seventeen study areas from 12 geographical locations in Malaysia were studied and grouped into seven habitat types given as primary forest, secondary forest, urban, monoculture, mixed forest of lowland and limestone, beach forest and mixed forest of secondary growth and orchard to reflect a portion of the vast tropical habitat. The average temperature for all the habitats ranges from 23°C to 28°C while rainfall measure range from 0.7 mm to 9.6 mm. There are no significant differences in the temperature and rainfall measures that could be used to discriminate them into different habitats accordingly. The diversity indices were calculated based on Shannon's diversity index (H') and Simpson's diversity index (1-D) using Multivariate Statistical Package (MVSP) version 3.0. Both indices reflect the highest bird diversity in mixed forest of the limestone and lowland habitat (H'= 3.698, 1-D = 0.969). A total of 2199 throat washing and blood samples were collected from 1132 birds. The samples were screened for the presence of viral RNA genome. Out of the total samples, 1797 were analysed using reverse transcriptase polymerase chain reaction (RT-PCR) and 402 samples were analysed by the immunocapture RT-PCR. Detection by RT PCR was carried out using H5, H6, H7, H9 and nucleoprotein (NP) primers while immunocapture to the microplate was conducted using serowell plates pre-coated with H5, H6, H7 and H9 antigens. The results of the detection were negative for all isolates. This probably suggests that birds in Malaysia are free from avian influenza A virus. Optimisation of the detection based on the two techniques had been carried out using positive control. Amplification and detection of viral RNA were optimised at the temperature of 70°C with the use of H5 gene. However, the potential hosts, preferred habitats as well as climatic factor (rainfall and temperature) that were associated to the transmission and infection of the AIV could not be discriminated with reference to the negative detection. Although all isolates were tested negative, the infection of avian influenza virus is still a major concern because the fact that birds are free moving organisms suggests that higher chances of interaction between the birds and other fauna including human is plausible.